1970
DOI: 10.1530/jrf.0.0230513
|View full text |Cite
|
Sign up to set email alerts
|

Lactation and Lactational Amenorrhoea With Post-Partum Iucd Insertions

Abstract: The post-partum period is considered as an ideal period for propagating any birth control technique as women are highly motivated and a number of them are under some medical care. For the introduction of an intra-uterine con-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1974
1974
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 1 publication
(2 reference statements)
0
5
0
Order By: Relevance
“…It should not be expected to have an effect on lactation (either positive or negative). Studies of lactation in women using the IUD confirm this 33,3545…”
Section: The Effect Of Iuds On Lactationmentioning
confidence: 79%
“…It should not be expected to have an effect on lactation (either positive or negative). Studies of lactation in women using the IUD confirm this 33,3545…”
Section: The Effect Of Iuds On Lactationmentioning
confidence: 79%
“…Those with IUDs lactated for 2 months longer on average than in previous lactations. In India, Hingorani & Bai (1970) found the average length of lactation in women fitted with IUDs to be 10-86 months, compared with 6-99 months in controls; but this difference was not statistically significant. There seems to be no evidence on amounts of milk secreted, with and without IUDs.…”
Section: Do Non-steroidal Methods Of Contraception Affect Lactation? mentioning
confidence: 88%
“…At the 8th IPPF International Conference in Santiago, Gomez-Rogers [Ill reported that lactating mothers using the IUCD had a significantly longer duration the infant. Combined oral contraceptives However, three other studies showed no should, therefore, not be recommended for significant changes in lactation in IUCD use during lactation -especially not before users [7, 14,16]. 6 months postpartum.…”
Section: Other Contraceptive Methodsmentioning
confidence: 99%